Evaluation of the antinociceptive effect of methanolic extract of Passiflora caerulea.L in adult male rat - M Zarei; S Mohammadi; M Asgari Nematian (Armaghane Danesh Bimonthly Journal, 2014)
Background & aim: In traditional medicine, Passiflora caerulea is used as a pain relieving and neurogenic malaise.‌ The aim of this study was to evaluate the analgesic efficacy of Passiflora caerulea extract in mature male rats.